The Influence of Environmental Concerns on Drivers Preferences for Electric Cars - Alexandros Dimitropoulos (Tinbergen Institute, 2014)
We examine the influence of drivers environmental concerns on their preferences for different types of plug-in electric vehicles (PEVs). Our empirical approach is built around the results of a large-scale survey among Dutch drivers, where preferences for electric vehicles are elicited through a choice experiment and environmental concerns are reflected in individual responses to Likert-type questions. On this basis, we develop advanced latent class models to study preference heterogeneity and its link to drivers socio-demographic background and environmental concerns. We find that environmental concerns are an important predictor of class membership and that highly concerned drivers tend to cluster in classes with a positive stand towards PEVs. High environmental concerns are positively associated with drivers age and education, while negatively related to d rivers household income.
Keywords: D12; O33; Q58; R41; 330; Latent class; Latent variable; Environmental concern; Electric vehicle; Plug-in hybrid